First report of the genus Anchorius Casey, 1900 (Coleoptera: Biphyllidae) in Chile, with description of a new species. - Francisco Tello; Cristóbal Tello-Arriagada (Revista Chilena de Entomología)
The genus Anchorius Casey, 1900 (Coleoptera: Biphyllidae) is reported for the first time in Chile. Based on the study of specimens from collections, Anchorius dollyae sp. nov. is described and illustrated. This new taxon is distinguished from other known Anchorius species by its distinctive distribution pattern of rows of pronotal setae, the presence of well-defined femoral lines and lateral lines of the first ventrite, incomplete metaventral discrimen, and different aedeagal morphology compared to morphologically similar species. This new species represents the southernmost record of this genus in South America. Finally, this finding provides new Anchorius habitat associations, including temperate and Mediterranean forests ecosystems in Chile.